2006
DOI: 10.1111/j.1460-9568.2006.04981.x
|View full text |Cite
|
Sign up to set email alerts
|

The Kölliker‐Fuse nucleus gates the postinspiratory phase of the respiratory cycle to control inspiratory off‐switch and upper airway resistance in rat

Abstract: Lesion or pharmacological manipulation of the dorsolateral pons can transform the breathing pattern to apneusis (pathological prolonged inspiration). Apneusis reflects a disturbed inspiratory off-switch mechanism (IOS) leading to a delayed phase transition from inspiration to expiration. Under intact conditions the IOS is irreversibly mediated via activation of postinspiratory (PI) neurons within the respiratory network. In parallel, populations of laryngeal premotoneurons manifest the IOS by a brief glottal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
259
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(296 citation statements)
references
References 64 publications
(73 reference statements)
34
259
2
1
Order By: Relevance
“…This implicitly supports the conclusion that both these rhythms are generated by network mechanisms without significant contribution of an I NaP -dependent intrinsic mechanism. Another conclusion drawn from these studies is that the input from the pons is necessary for the expression of the postinspiratory activity in the network and the three-phase rhythm (at least in the absence of pulmonary stretch receptor inputs as in the in situ preparation), which supports previous findings (Rybak et al, 2004a;Dutschmann and Herbert, 2006). Based on our experimental studies we also conclude that removal of neural circuits rostral to pre-BötC decreases the role of inhibitory network interactions (provided by the expiratory populations of BötC) and increases the role of the endogenous I NaP -dependent rhythmicity in the pre-BötC network.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This implicitly supports the conclusion that both these rhythms are generated by network mechanisms without significant contribution of an I NaP -dependent intrinsic mechanism. Another conclusion drawn from these studies is that the input from the pons is necessary for the expression of the postinspiratory activity in the network and the three-phase rhythm (at least in the absence of pulmonary stretch receptor inputs as in the in situ preparation), which supports previous findings (Rybak et al, 2004a;Dutschmann and Herbert, 2006). Based on our experimental studies we also conclude that removal of neural circuits rostral to pre-BötC decreases the role of inhibitory network interactions (provided by the expiratory populations of BötC) and increases the role of the endogenous I NaP -dependent rhythmicity in the pre-BötC network.…”
Section: Discussionsupporting
confidence: 78%
“…5A, B. Based on indirect evidence about a strong excitatory influence of the pons on the post-I neurons (Rybak et al, 2004a;Dutschmann and Herbert, 2006), we have suggested that with the removal of the pons and adjacent medullary regions, all post-I populations of BötC lose a significant portion of the excitatory drive (see Fig. 3B), whereas the drive to aug-E(2) is less dependent on these regions.…”
Section: Computational Modeling Of the Brainstem Respiratory Networkmentioning
confidence: 99%
“…Recent evidence supports a role for the pons: microtransection studies in rat that eliminated the pons abolished post-I recorded from cVN (25,26). Moreover, glutamate stimulation of Kölliker-Fuse (KF) neurons caused a prolongation of post-I recorded from the recurrent laryngeal nerve of juvenile rats in situ, whereas GABA receptor activation at the identical injection sites completely suppressed post-I activity (27). In addition, there is evidence that medullary sites also play a role.…”
Section: Insufficient Gaba a Inhibition Underlies Tonic Activity In Ementioning
confidence: 95%
“…8, B, B1, and B2. Based on experimental evidence that stimulation of the dorsolateral pons (PB/KF region) provides strong activation of post-I neurons (Dutschmann and Herbert 2006;Rybak et al 2004a), we suggested that a major portion of excitatory tonic drive to post-I neurons of BötC comes from the pons. In contrast, the aug-E population in the model is less dependent on pontine drive but receives a major excitatory drive from the RTN and other medullary sources.…”
Section: Modeling Reorganization Of Rhythm Generating Mechanisms Aftementioning
confidence: 99%